11ß-Hydroxysteroid dehydrogenase type 1, brain atrophy and cognitive decline - MacLullich, Alasdair MJ (2010)
Excess cortisol levels are linked with brain atrophy and cognitive decline in older people. 11ß-hydroxysteroid dehydrogenase type 1 (11ß-HSD1) potently amplifies intracellular glucocorticoid action by converting inert cortisone to active cortisol, but any causal importance in brain ageing is unexplored. We tested the hypotheses that higher systemic 11ß-HSD1 activity predicts brain atrophy and cognitive decline in older men. In a longitudinal study of 41 men (65-70y at baseline) we measured baseline systemic 11ß-HSD1 activity, the urinary 5alpha- and 5beta-tetrahydrocortisol to tetrahydrocortisone ratio (THFs/THE), and assessed change in brain atrophy, white matter lesions and cognitive function over six years. Baseline THFs/THE correlated negatively with baseline hippocampal volumes (left: r=-0.37; right: r=-0.34; p<0.05) and positively with ventricular volumes (r=0.43, p=0.006) and periventricular white matter lesions (rho=0.31, p=0.047). Importantly, baseline THFs/THE but not cortisol predicted increase in ventricular volumes (r=0.33, p=0.037) and decline in processing speed (r=-0.55, p=0.0002) over six years. The predictive link between systemic 11β-HSD1 activity and progressive brain atrophy and cognitive decline suggests 11β-HSD1 inhibition as a plausible therapy for brain ageing.